Theoretical ecology : principles and applications - May, Robert M., (Robert McCredie), 1936-; McLean, Angela R. (New York : Oxford University Press, 2007)
Provides a concise overview of ecological science, bridging theory and practice, describing the ways interacting populations of plants and animals change over time and space and discussing applications of such concepts to practical issues such as fisheries, infectious diseases, food supply, and climate change.
Includes bibliographical references (p. 216-248) and index.
Adult
Keywords: Ecology; Ecology